Abstract ID: 155 OpenDose: A collaborative effort to produce reference dosimetric data with Monte Carlo simulation software. (October 2017) - Chauvin, Maxime; Borys, Damian; Botta, Francesca; Bzowski, Pawel; Coca Pérez, Marco A.; Cremonesi, Marta; Dabin, Jérémie; Denis-Bacelar, Ana M.; Desbrée, Aurélie; Bitar, Ziad El; Falzone, Nadia; Ferrer, Ludovic; et al.
Abstract : Radiopharmaceutical dosimetry for diagnostic and therapy uses reference data describing energy deposition from a source to target tissues. Reference data are usually expressed as S-values, i.e. mean absorbed dose in a target from a source decay (Gy.Bq -1 .s -1 ). The OpenDose project aims at providing an open database of robust reference S-values generated from different Monte Carlo (MC) software, through an international collaboration. The ICRP 110 reference adult female[1] was chosen as the first model, with 140 segmented tissues-organs and a voxel size of 1.775 × 1.775 × 4.84 mm 3 . Specific Absorbed Fractions (SAFs) are being computed for different sources, with mono-energetic photons and electrons. S-values will be generated by interpolating these mono-energetic SAFs for isotope decay schemes[2] . Producing data with different software using various physics lists will allow a cross-verification of the results and their associated uncertainties. The OpenDose project already includes 12 research teams and 5 of the most popular MC software used in radiopharmaceutical dosimetry: Geant4/GATE, Fluka, EGSnrc/EGS++, MCNP/MCNPX and Penelope. A total of 46 source tissues-organs have so far been simulated with GATE for mono-energetic particles (photons + electrons) from 5 keV to 10 MeV. Each simulation requires ∼ 1 day of computation on a single CPU for 10 8 primary particles and produces a 3D map (voxel-based) of absorbed doses and uncertainties. When available, the data from the other software will be analysed and compared in terms of SAFs for different targets and energies. Next steps include the integration of SAFs to provide S-values and build the database to allow Nuclear Medicine centres to easily access and use the data. Through a collaboration of research teams using different MC techniques, we are developing a freely accessible database of reference dosimetric data. A preliminary study using the ICRP adult female model is ongoing. The project is open to new research teams to increase the variety of software and will expand to more computational models and studies.